Experience capitalization: The end of a project is just the beginning - Tukundane, Nelson (Technical Centre for Agricultural and Rural Cooperation, 2019)
Learning from experience. That's what it's all about. My first experience capitalization workshop in Nairobi changed the way I want to work. As a representative of the Uganda National Farmers Federation (UNFFE), I was given the opportunity to participate in a workshop organised by CTA for members of the Eastern Africa Farmers Federation (EAFF). During this workshop, I realised that our own experiences count, but also that I could learn from other regions in the world, and even, that others could learn from our experiences! How to capture the challenges, replicate the successes, and avoid making the same mistakes – these were some of the questions we addressed.